Single-cell RNAseq identifies clonally expanded antigen-specific T-cells following intradermal injection of gold nanoparticles loaded with diabetes autoantigen in humans - Hanna, Stephanie J.; Thayer, Terri C.; Robinson, Emma J. S.; Vinh, Ngoc-Nga; Williams, Nigel; Landry, Laurie G.; Andrews, Robert; Siah, Qi Zhuang; Leete, Pia; Wyatt, Rebecca; McAteer, Martina A.; Nakayama, Maki; et al. (Frontiers in Immunology, 2023)
Gold nanoparticles (GNPs) have been used in the development of novel therapies as a way of delivery of both stimulatory and tolerogenic peptide cargoes. Here we report that intradermal injection of GNPs loaded with the proinsulin peptide C19-A3, in patients with type 1 diabetes, results in recruitment and retention of immune cells in the skin. These include large numbers of clonally expanded T-cells sharing the same paired T-cell receptors (TCRs) with activated phenotypes, half of which, when the TCRs were re-expressed in a cell-based system, were confirmed to be specific for either GNP or proinsulin. All the identified gold-specific clones were CD8 + , whilst proinsulin-specific clones were both CD8 + and This is a provisional file, not the final typeset article CD4 + . Proinsulin-specific CD8 + clones had a distinctive cytotoxic phenotype with overexpression of granulysin (GNLY) and KIR receptors. Clonally expanded antigen-specific T cells remained in situ for months to years, with a spectrum of tissue resident memory and effector memory phenotypes. As the T-cell response is divided between targeting the gold core and the antigenic cargo, this offers a route to improving resident memory T-cells formation in response to vaccines. In addition, our scRNAseq data indicate that focusing on clonally expanded skin infiltrating T-cells recruited to intradermally injected antigen is a highly efficient method to enrich and identify antigen-specific cells. This approach has the potential to be used to monitor the intradermal delivery of antigens and nanoparticles for immune modulation in humans.